Solution thermodynamics and preferential solvation of sulfamethazine in (methanol + water) mixtures (2016)
The solubility of sulfamethazine (SMT) in {methanol (1) + water (2)} co-solvent mixtures was determined at five different temperatures from (293.15 to 313.15) K. The sulfonamide exhibited its highest mole fraction solubility in pure methanol (d1 = 29.6 MPa1/2) and its lowest mole fraction solubility in water (d2 = 47.8 MPa1/2) at each of the five temperatures studied. The Jouyban-Acree model was used to correlate/predict the solubility values. The respective apparent thermodynamic functions Gibbs energy, enthalpy, and entropy of solution were obtained from the solubility data through the van't Hoff and Gibbs equations. Apparent thermodynamic quantities of mixing were also calculated for this drug using values of the ideal solubility reported in the literature. A non-linear enthalpy-entropy relationship was noted for SMT in plots of both the enthalpy vs. Gibbs energy of mixing and the enthalpy vs. entropy of mixing. These plots suggest two different trends according to the slopes obtained when the composition of the mixtures changes. Accordingly, the mechanism for SMT transfer processes in water-rich mixtures from water to the mixture with 0.70 in mass fraction of methanol is entropy driven. Conversely, the mechanism is enthalpy driven in mixtures whenever the methanol composition exceeds 0.70 mol fraction. An inverse Kirkwood-Buff integral analysis of the preferential solvation of SMT indicated that the drug is preferentially solvated by water in water-rich mixtures but is preferentially solvated by methanol in methanol-rich mixtures. © 2016 Elsevier Ltd. All rights reserved.